Exploring Selected Game on English for Young Learner’s Vocabulary Mastery: The Word Clap Vs Quiz - Desi Nori Sahputri; Kurniawan Kurniawan (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
This research was conducted to offer an alternative teaching strategy on raising vocabulary mastery using the Word Clap Game. The purpose of this study was to determine whether there was a difference in the results of the Word Clap Game strategy on EYL’s vocabulary mastery of the fifth-grade Narwastu elementary school in Pekanbaru, Indonesia. This quasi experiment research involved 60 students with two classes; The experimental class with 29 students (VB class) and the control class with 31 students (VA class). The results of this study highlighted the post-test scores in the experimental class as having increased compared with the pre-test scores, which can be seen from the average score of the experimental class post-test that was 76.03 while the pre-test was 62.75. The average post-test value in the control class is 74.19, which was lower than the experimental class. Therefore, this study believes that there was no significant difference in students who are taught using the Word Clap Game strategy in mastering vocabulary with students who were not taught using the Word Clap Game strategy both seem effective in raising the EYL vocabulary mastery.